2020
DOI: 10.21203/rs.3.rs-31015/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibacterial Activity of cLFchimera and its Synergistic Potential with Antibiotics against Some Foodborne Pathogens Bacteria

Abstract: Background: Frequent and unlimited use of antibiotics caused the development of antibiotic resistance by microorganisms. Therefore, there is an argent need to discover novel antibacterial agents or a combination of agents as a safe treatment strategy for various infections. The aim of the present study was to evaluate the synergistic effects of cLFchimera, an antimicrobial peptides (AMPs), and antibiotics on several foodborne bacterial strains. Methods: A checkerboard method was used to determine the synergist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Roshanak et al 54 demonstrated that the increase of 260 nm absorbing materials from P. aeruginosa PTCC 1707, E. coli ATCC 25922, and Salmonella typhi PTCC 1609 with treatment by gentamycin had a damaging effect on the cell wall and exhibited viscidity, and most of the outermost layer of the bacterial cells disappeared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roshanak et al 54 demonstrated that the increase of 260 nm absorbing materials from P. aeruginosa PTCC 1707, E. coli ATCC 25922, and Salmonella typhi PTCC 1609 with treatment by gentamycin had a damaging effect on the cell wall and exhibited viscidity, and most of the outermost layer of the bacterial cells disappeared.…”
Section: Discussionmentioning
confidence: 99%
“…The observed increase in ODs readings from 0.54 to 1.73 compared to control cells indicates cell membrane damage. These results were in accordance with Al-Shuneigat et al52 where methicillin-resistant Staphylococcus aureus(ATCC 43300), P. aeruginosa (ATCC 27853), and Staphylococcus epidermidis (ATCC 35984) were treated at MIC of Achillea biebersteinii essential oils showing a continual increase in the concentration of 260 nm absorbing materials over 300 min of incubation, indicating that the cell membrane structure was damaged and caused release of intracellular materials including nucleic acids to the outer solution as compared to the control group where the hydrophobicity of plant extracts allowing them to penetrate into microbial cells and accumulate inside the cells, causing disturbance to their structure that results in increased cellular leakage and death.Also, the results of this study were in compatibility with those obtained by Imelda et al,53 where the absorbance at 260 nm of the supernatant of Escherichia coli and S. aureus suspensions increased obviously after 30 min of exposure to the extract of the P. minus leaves, indicating that cell materials were released outside the cells by disturbing membrane permeability, which induced leakage of the cytoplasmic contents.Roshanak et al54 demonstrated that the increase of 260 nm absorbing materials from P. aeruginosa PTCC 1707, E. coli ATCC 25922, and Salmonella typhi PTCC 1609 with treatment by gentamycin had a damaging effect on the cell wall and exhibited viscidity, and most of the outermost layer of the bacterial cells disappeared.…”
mentioning
confidence: 99%
“…These small, naturally occurring compounds have a wide range of antibacterial activity and several modes of action, which reduces the likelihood of resistance evolution. AMPs are essential elements of the innate immune system in various organisms, acting as the first line of defense against pathogens (6). In addition, AMPs can stimulate cells to produce chemokines, stimulate angiogenesis, accelerate wound healing, and affect programmed cell death in multicellular organisms (7).…”
Section: Introductionmentioning
confidence: 99%